2021
DOI: 10.1111/jocn.15950
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance bands exercise for frail older adults: A systematic review and meta‐analysis of randomised controlled studies

Abstract: Aims and Objectives:Research examining the effectiveness of resistance band exercises for improving physical and psychological dimensions among frail older adults has been inconsistent. We aimed to examine the effects of resistance band exercises for improving outcomes in frail older adults. Background:To provide robust evidence regarding the effectiveness of resistance band exercises and explore other potential outcomes in frail older adults, a systematic review of RCTs remains necessary.Design: Systematic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…However, evidence around potential interventions for IC maintenance/increase remains scarce [ 18 ]. Multicomponent physical exercise (MCE) (comprising strength, aerobic, gait and balance and flexibility exercises), given its proven benefits on several proposed markers of individual domains of IC (locomotion [ 19 , 20 ], cognitive [ 21 ], psychology [ 22 ]), has been suggested as a fundamental intervention for healthy ageing in different populations of older adults [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence around potential interventions for IC maintenance/increase remains scarce [ 18 ]. Multicomponent physical exercise (MCE) (comprising strength, aerobic, gait and balance and flexibility exercises), given its proven benefits on several proposed markers of individual domains of IC (locomotion [ 19 , 20 ], cognitive [ 21 ], psychology [ 22 ]), has been suggested as a fundamental intervention for healthy ageing in different populations of older adults [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many interventions have attempted to change the building blocks of frailty such as strength and gait speed, ( 3 , 32 , 33 ) and those indicators that were targeted by the intervention did change but the impact on frailty classification was small or nil.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant benefit of resistance exercise is its positive effect on falls and functional disorders, which are risk factors related to osteoporosis and sarcopenia [ 21 ]. A recent meta-analysis study reported that resistance exercise using elastic bands was effective for obese older women [ 22 ]. The present study aimed to examine the effects of 24-week resistance exercise training on body composition, BMD, functional fitness, and isokinetic muscle strength in obese older women.…”
Section: Introductionmentioning
confidence: 99%